2018
DOI: 10.1111/desc.12758
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of facial emotion processing in infancy

Abstract: In the present study we examined the neural correlates of facial emotion processing in the first year of life using ERP measures and cortical source analysis. EEG data were collected cross-sectionally from 5-(N = 49), 7-(N = 50), and 12-month-old (N = 51) infants while they were viewing images of angry, fearful, and happy faces.The N290 component was found to be larger in amplitude in response to fearful and happy than angry faces in all posterior clusters and showed largest response to fear than the other two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
133
7
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 97 publications
(158 citation statements)
references
References 61 publications
13
133
7
2
Order By: Relevance
“…At least one fMRI study in adults (Zhang et al, 2016) and another fNIRS study in infants (Grossmann et al, 2018) also do not report differential activations to different types of facial emotions over temporal cortices. Interestingly, and contrary to previous reports in behavioral and ERP paradigms Xie et al, 2018), no differences between 5-and 7-month-olds were found. Because ERP and fNIRS paradigm differ in paradigm design, response temporality, and underlying neural sources, some or all of these differences may account for the differences in findings.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…At least one fMRI study in adults (Zhang et al, 2016) and another fNIRS study in infants (Grossmann et al, 2018) also do not report differential activations to different types of facial emotions over temporal cortices. Interestingly, and contrary to previous reports in behavioral and ERP paradigms Xie et al, 2018), no differences between 5-and 7-month-olds were found. Because ERP and fNIRS paradigm differ in paradigm design, response temporality, and underlying neural sources, some or all of these differences may account for the differences in findings.…”
Section: Discussioncontrasting
confidence: 99%
“…fNIRS has also revealed that medial frontal regions are implicated in processing happy faces in infants from 9-13 months (Minagawa-Kawai et al, 2009) and linked individual differences in frontal responses to emotional faces with earlier epigenetic changes (Krol et al, 2019) and later behavior (Grossmann et al, 2018). However, no studies to date have directly tested for differences in neural activity between 5 and 7 months, a critical time window during which differential responses to fearful faces are often first observed with ERP (Leppänen, Richmond, Vogel-Farley, Moulson, & Nelson, 2009;Xie, McCormick, Westerlund, Bowman, & Nelson, 2018). In addition, no prior infant fNIRS study has examined responses to facial emotions when facial identity varies, a focus of classic behavioral studies in this age group (Bayet & Nelson, 2019;), or in relation to simultaneous looking behavior to facial features.…”
mentioning
confidence: 99%
“…Additionally, differential processing of emotional faces was also found in a recent cross-sectional study comparing the amplitude of the N290 and P400 components and determining their specific cortical sources in 5-, 7-, and 12-month-old infants while they were viewing angry, fearful, and happy faces (Xie et al, 2018).…”
Section: Discussionmentioning
confidence: 72%
“…Further studies examining the N290 found it to be larger in response to fearful compared to angry faces (Hoehl & Striano, ) and happy faces (van den Boomen, Munsters, & Kemner, ). Additionally, differential processing of emotional faces was also found in a recent cross‐sectional study comparing the amplitude of the N290 and P400 components and determining their specific cortical sources in 5‐, 7‐, and 12‐month‐old infants while they were viewing angry, fearful, and happy faces (Xie et al, ). Indeed, regardless of infants' age, N290 responses were greater to fearful and happy faces compared to angry expressions, and while P400 responses were found to be greater in response to angry than happy and fearful faces.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation